From IBS to DBS: The Dysbiotic Bowel Syndrome. (5th May 2016) - Benno, Peter; Dahlgren, Atti-La; Befrits, Ragnar; Norin, Elisabeth; Hellström, Per M.; Midtvedt, Tore
Irritable bowel syndrome is a chronic gastrointestinal disorder characterized by abdominal pain and altered bowel habits in the absence of organic disease. We present 2 cases where diarrhea-predominant irritable bowel syndrome occurred in association with earlier intestinal infection or antibiotic treatment. Both were successfully treated with instillation of an anaerobic cultivated human intestinal microbiota. Thereafter, they were symptom free for at least 12 months. We now introduce the term dysbiotic bowel syndrome covering cases where a disturbed intestinal microbiota is assumed to be present. We recommend that restoration of the dysbiotic gut microbiota should be first-line treatment in these conditions.